An introduction to language - Fromkin, Victoria; Rodman, Robert; Hyams, Nina M. 1952- (Cengage, 2017)
AN INTRODUCTION TO LANGUAGE, 11th Edition, offers an entirely up-to-date look at language studies and linguistics in today's world. Written from the ground up as if it were a first edition, the book is fresh, modern, and reflective of the current state of the field. At the same time, it maintains the acclaimed light, friendly, readable style and the breadth of coverage that have made it a perennial best seller. The authors examine grammatical subjects (e.g., morphology, syntax, semantics, phonetics, phonology), childhood language development and adult secondary language acquisition, and the tremendous leap in knowledge achieved in neurolinguistics. -- Publisher's website